Diagnostic Accuracy of Ultrasonography in Detecting Ureteric Calculi in Patients with Renal Colic Taking Non-Contrast Multidetector Computerized Tomography of Kidney, Ureter, and Bladder (CT KUB) as the Gold Standard - Lalchan, Subita; Sharma, Prakash; KC, Subash; Gyawali, Merina; Poudel, Aseem (Nepal Journal of Medical Sciences, 2022)
Introduction: The goal of this study is to find the sensitivity, specificity, and diagnostic accuracy of ultrasonography in detecting ureteric calculi in patients with renal colic taking NECT KUB as the gold standard. Methods: All patients with acute renal colic presenting in the radiology department for ultrasonography and NECT KUB were enrolled in the study. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of ultrasonography in detecting ureteric calculi were calculated by taking NECT KUB as the gold standard test. Results: A total of 88 patients were enrolled in the study. The mean age was 37 years. The sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of ultrasonography for the detection of ureteric calculi were found to be 85.8 %, 80 %, 97.1 %, 42.1 %, and 85.2 % respectively in the present study. Conclusion: Ultrasonography shows high sensitivity and specificity for the diagnosis of ureteric calculi. It is a cheap, non-invasive, and easily available modality and there is no risk of radiation exposure. NECT KUB should be reserved for that patient for whom ultrasonography is not able to give a diagnosis.